Analysis of Management Systems in Wastewater Processing at Regional Public Hospital in Teluk Kuantan 2018 - Marian Tonis; Henni Djuhaeni; Arnawilis Arnawilis (STIKes Hang Tuah Pekanbaru, 2020)
Wastewater Treatment Plant (WWTP/IPAL) is a building that functions to derived from activities in health care facilities. In Teluk Kuantan Regional General Hospital (RSUD), wastewater treatment has not work according to the procedure because of a leak in the IPAL pipelines. The objective of research is to provide in-depth information about the analysis of management elements and management functions in Wastewater Treatment at Regional General Hospital in Taluk Kuantan, 2018. This research uses qualitative research with explorative approach, in Regional General Hospital in Taluk Kuantan. There were 5 informants, Head of Infrastructure Facilities, Social Sciences, Management Staff and 2 staff of IPAL. The research used the interviews, observation, and documents. Data processing was done by data reduction, data presentation, and conclusion. Validation data was used source, triangulation method and triangulation data. The result of research get important themes, namely: Inadequate Human Resources (lack of 2 special staffs) and has not been according to basic knowledge (no one was sanitation and environmental health, planning of management to management elements and management functions). IPAL has not been carried out in all and organizing at Wastewater Treatment Plants has not implemented. So, there is duplicate work causes a loss of less optimal. It is recommended that wastewater management should be carried out by managing the elements of management and management functions. In order for management of wastewater is organized and be better.